2017
DOI: 10.1016/j.jadohealth.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Youth Substance Use Disparities: Results From a Population-Based Sample

Abstract: Using data from the first representative study of youth to include a measure of gender identity, we show that transgender youth are at heightened risk for substance use compared with nontransgender peers. Future research is needed to identify the structural and psychosocial mechanisms that drive these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
179
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 266 publications
(201 citation statements)
references
References 26 publications
18
179
1
3
Order By: Relevance
“…16 Emerging evidence suggests disparities in emotional distress and substance use are partially explained by peer victimization and depressive symptoms, 2,4,7 consistent with the minority stress model. 8,9 Focusing on these disparities masks the reality that some TGD youth are doing well and have supports to thrive.…”
Section: Introductionmentioning
confidence: 85%
“…16 Emerging evidence suggests disparities in emotional distress and substance use are partially explained by peer victimization and depressive symptoms, 2,4,7 consistent with the minority stress model. 8,9 Focusing on these disparities masks the reality that some TGD youth are doing well and have supports to thrive.…”
Section: Introductionmentioning
confidence: 85%
“…Studies have shown that TGD youth in particular have elevated risk of emotional distress, substance use and bullying victimisation compared with cisgender adolescents (Clark et al, ; Eisenberg et al, ; Perez‐Brumer, Day, Russell, & Hatzenbuehler, ; Veale, Watson, Peter, & Saewyc, ). Disparities extend to access to and utilisation of healthcare (Clark, Veale, Greyson, & Saewyc, ; Day, Fish, Perez‐Brumer, Hatzenbuehler, & Russell, ; Eisenberg et al, ; Rider, McMorris, Gower, Coleman, & Eisenberg, ; Veale et al, ). As adolescence is a time of rapid physical growth, identity development and establishment of lasting health behaviours (Sawyer et al, ; Shlafer et al, ), going without healthcare during this period can result in unchecked health behaviours that contribute to chronic disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A well-established body of literature has documented disparities in substance use for lesbian, gay, and bisexual (LGB)* young people. [1][2][3][4][5] Although substance use in and of itself is not always problematic, research has indicated that harmful substance use behaviors (e.g., drinking heavily) among adolescents have been linked to academic, physical, and social problems. 6 Growing evidence indicates that dis-parities in substance use behaviors are widening for some sexual minority (e.g., LGB) young people.…”
Section: Introductionmentioning
confidence: 99%